Yugoslav self-management: The forgotten anti-capitalist seeds of degrowth - Kočović De Santo, Milica (Cultura Económica, 2024)
This research investigates the historical significance of self-management practices in Yugoslavia as inherently anti-capitalist and anti-colonial, contributing to the discourse on degrowth. The primary argument posits that Yugoslav self-management embodies unwritten historical elements that resonate with contemporary degrowth theory. Employing a theoretical and methodological framework that encompasses desk research, historical methods, and institutional analysis, this study utilizes Erik Olin Wright’s anti-capitalist strategic framework to delineate the unique characteristics of Yugoslav self-management in contrast to other forms. The findings suggest that the Yugoslav model offers relevant insights for future provisioning systems in a post-growth and post-development context.